In vivo transcriptomes of Streptococcus suis reveal genes required for niche-specific adaptation and pathogenesis - Jesús Arenas; Ruth Bossers-de Vries; José Harders-Westerveen; Herma Buys; Lisette M. F. Ruuls-van Stalle; Norbert Stockhofe-Zurwieden; Edoardo Zaccaria; Jan Tommassen; Jerry M. Wells; Hilde E. Smith; Astrid de Greeff (Virulence, 2019)
Streptococcus suis is a Gram-positive bacterium and a zoonotic pathogen residing in the nasopharynx or the gastrointestinal tract of pigs with a potential of causing life-threatening invasive disease. It is endemic in the porcine production industry worldwide, and it is also an emerging human pathogen. After invasion, the pathogen adapts to cause bacteremia and disseminates to different organs including the brain. To gain insights in this process, we infected piglets with a highly virulent strain of S. suis, and bacterial transcriptomes were obtained from blood and different organs (brain, joints, and heart) when animals had severe clinical symptoms of infection. Microarrays were used to determine the genome-wide transcriptional profile at different infection sites and during growth in standard growth medium in vitro. We observed differential expression of around 30% of the Open Reading Frames (ORFs) and infection-site specific patterns of gene expression. Genes with major changes in expression were involved in transcriptional regulation, metabolism, nutrient acquisition, stress defenses, and virulence, amongst others, and results were confirmed for a subset of selected genes using RT-qPCR. Mutants were generated in two selected genes, and the encoded proteins, i.e., NADH oxidase and MetQ, were shown to be important virulence factors in coinfection experiments and in vitro assays. The knowledge derived from this study regarding S. suis gene expression in vivo and identification of virulence factors is important for the development of novel diagnostic and therapeutic strategies to control S. suis disease.